Effect of local chemistry on the thermodynamic modeling of multicomponent alloys for hydrogen storage - Pedroso, Otávio Abreu (Universidade Federal de São Carlos, 2025)
In this work, a new thermodynamic model for pressure-composition-temperature diagram (PCT) calculations of multicomponent alloys for hydrogen storage was developed and evaluated. The objective of this new model is to evaluate the local chemical effect, that is, the interaction between hydrogen and the first neighbors of the interstitial sites, in the PCT diagrams. Initially, a site blocking model based on the Johnson-Mehl-Avrami (JMAK) equation was proposed to quantify the configurational entropy, taking into account the interstitial sites blocked due to the prior occupation of a nearby neighbor site by hydrogen. The model effectively calculates the fractions of blocked sites, avoiding blocking overlaps that can occur in the studied structures, allowing the accurate determination of partial molar entropy, which showed good agreement with experimental data. A Discrete Site Energy model (DSE) was proposed and implemented in open source code to calculate the thermodynamic properties for metal-hydrogen systems under para-equilibrium conditions. The model considers the different local chemical environments at the interstitial sites of crystalline structures. The model then calculates the Gibbs free energy as a function of the distribution of occupation of the different interstitial sites present in the alloys, which can be determined by minimizing the Gibbs free energy as a function of the fraction of interstitial occupied sites. This model was developed for two classes of multicomponent alloys important for hydrogen storage, alloys with a body-centered cubic (BCC) structure and alloys with a C14-type Laves phase structure. For BCC structures, a validation process was performed using a set of alloys from the TiVNbCr-system, where the calculated results observed describe the plateau pressure well. The DSE model was subsequently applied to C14 Laves phases, where interstitial sites are described by seven distinct Wyckoff positions that introduce cross-blocking effects and distinct local chemical environments depending on the Wyckoff position. After optimizing the metal-hydrogen interaction energies, the model showed good agreement with the experimental results for five C14 alloys. In addition, it was possible to observe the sensitivity of the model to minor energy deviations, attributed to the logarithmic relationship between pressure and the chemical potential of H. These models provide a computationally efficient framework for screening alloy compositions, thereby reducing experimental costs in the design of hydrogen storage materials. The JMAK approaches to site blocking effect and DSE demonstrate versatility across crystal structures, offering critical insights into site-blocking dynamics and phase equilibrium for H storage systems.
Efeito da química local na modelagem termodinâmica de ligas multicomponentes para armazenamento de hidrogênio
Keywords: Modelagem termodinâmica; Armazenamento de hidrogênio; Ligas multicomponente; Fases CCC; Fases de Laves C14; Thermodynamic model; Hydrogen storage; Multicomponent alloys; BCC phase; C14 Laves phase; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA